Material Ramah Lingkungan Pada Gedung Layanan Paru Rsud Siti Fatimah: Evaluasi Dan Rekomendasi - Saptaprima, Nyimas Siti Yuliani; Fitriani, Heni; Hadinata, Febrian (Syntax Literate, 2025)
The use of environmentally friendly materials in hospital contruction is essential to support sustainability and promote a healthier built environment. This study aims to analyze the practical application of green materials in the construction of the Pulmonary Service Building at RSUD Siti Fatimah, Palembang. A descriptive qualitative approach was employed, combining content analysis of technical document (Bill of Quantity and Technical Specifications) with quantitative data gathered from questionnaires distributed to construction proffesionals involved in the project. The materials were assessed based on six sustainability indicators: local materials, certified materials, recycled and reused materials, renewble materials, prefabricated materials, and materials free from hazardous substances. The findings indicate that local and certtified materials are the most commonly implemented, while the use of recycled and renewable materials remains limited. There is also a variation in understanding among professions, with architects and engineers demonstrating higher awareness compared to supporting roles. Material mapping revealed that the majority of structural and architectural components met some green criteria, though not optimally. Key barriers to implementation include limited material availability, higher costs, and lack of strong internal policy. This studi recommends enhancing green construction awareness, improving policy enforcement, and promoting the broader use of environmentally friendly materials in hospital building projects.